Final Answer:
The solution to the equation -3(h + 5) + 2 = 4(h + 6) - g is h = -12 and g = -18.
Step-by-step explanation:
Distribute the negative signs:
-3(h + 5) + 2 = -3h - 15 + 2
Combine constant terms:
-3h - 15 + 2 = 4(h + 6) - g
-3h - 13 = 4h + 24 - g
Isolate h on one side:
-7h - 13 = 24 - g
-7h = 37 - g
h = (37 - g) / -7
Substitute h back into the original equation to solve for g:
-3(h + 5) + 2 = 4(h + 6) - g
-3((37 - g) / -7 + 5) + 2 = 4((37 - g) / -7 + 6) - g
-3(-12 - g + 35) + 2 = 4(-12 - g + 42) - g
Simplify both sides:
11g + 66 = -36g + 108
47g = 42
g = -18
Therefore, the solution is h = -12 and g = -18.